2011
DOI: 10.1371/journal.pone.0023726
|View full text |Cite
|
Sign up to set email alerts
|

Pilot, Randomized Study Assessing Safety, Tolerability and Efficacy of Simplified LPV/r Maintenance Therapy in HIV Patients on the 1st PI-Based Regimen

Abstract: ObjectivesTo compare the efficacy and safety of an individualized treatment-simplification strategy consisting of switching from a highly-active anti-retroviral treatment (HAART) with a ritonavir-boosted protease inhibitor (PI/r) and 2 nucleoside reverse-transcriptase inhibitors (NRTIs) to lopinavir/ritonavir (LPV/r) monotherapy, with intensification by 2 NRTIs if necessary, to that of continuing their HAART.MethodsThis is a one-year, randomized, open-label, multi-center study in virologically-suppressed HIV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…Moreover, in contrast to previous studies, patients with a history of VF while on a PI-based regimen were enrolled, and there was no previous period in which tolerance to LPVr was determined before the start of monotherapy. Despite these facts, the virological efficacy was similar to that observed in clinical trials of mtLPVr (6,7,(9)(10)(11)(12)(13). It is noteworthy to mention that neither a history of VF on an unboosted or ritonavir-boosted PI-containing regimen nor the presence of minor resistance mutations to LPVr nor the once-daily administration of LPVr had negative influences on the virological outcome.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, in contrast to previous studies, patients with a history of VF while on a PI-based regimen were enrolled, and there was no previous period in which tolerance to LPVr was determined before the start of monotherapy. Despite these facts, the virological efficacy was similar to that observed in clinical trials of mtLPVr (6,7,(9)(10)(11)(12)(13). It is noteworthy to mention that neither a history of VF on an unboosted or ritonavir-boosted PI-containing regimen nor the presence of minor resistance mutations to LPVr nor the once-daily administration of LPVr had negative influences on the virological outcome.…”
Section: Discussionsupporting
confidence: 64%
“…Notwithstanding, a considerable proportion of patients maintained an undetectable viremia on lopinavirritonavir maintenance monotherapy (mtLPVr) and could benefit from a simpler regimen without nucleoside analogues or other antiretroviral drugs. Moreover, lack of adherence has been indicated as the main reason for virological failure (VF) in different studies (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Median CD4 + T-cell count at nadir was 215 cell/mm 3 (IQR 116-336). In 50 participants (22%), CD4 + T-cell count at nadir was ≤100 cells/mm 3 + T-cell count was ≤350 cells/mm 3 ; duration of viral suppression <50 copies/ml before switch was of 47 months (IQR 20-73). A total of 52 (23%) individuals previously failed virologically to a PI-based regimen (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been evaluated in a number of clinical trials including also HCV-coinfected individuals [1][2][3][4], but currently there are still no conclusive data on the efficacy and toxicity of such a regimen in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Simplification to PI/r monotherapy in fully suppressed patients might avoid the long-term effects of the NRTIs. Although initially considered a promising strategy, some studies showed a higher rate of low-level viremia (up to 12 % of participants) resulting in the need of reintroducing NRTIs [63][64][65]. The addition of 3TC to a PI/r was proposed in order to increase dual therapy efficacy [66].…”
Section: Simplificationmentioning
confidence: 99%